MANAGEMENT OF LEARNING ASSESSMENT USING CURRICULUM 2013 (CASE STUDY IN ISLAMIC PRIMARY SCHOOL (MI) MUHAMMADIYAH 5 WONOASRI PONOROGO - EAST JAVA - INDONESIA) - Afiful Ikhwan (MUADDIB Jurnal Kependidikan dan Keislaman, 2018)
The teaching and learning process really requires an assessment to find out the effectiveness of the learning that has been done. Assessment in the learning process aims to determine various issues related to development and reciprocity, so that learning is expected to be oriented towards developing an assessment of the quality of learning in school. The results of the assessment can be used by the teacher to improve learning activities. In this case, the assessment must be seen as an important thing that can give ideas for the teacher to carry out further learning. General subjects in MI Muhammadiyah 5 Wonoasri use the KTSP curriculum. In line with the characteristics of the competency-based curriculum that is oriented to mastery of competencies, the assessment system applied is in the form of a competency-based assessment system. Thus the standard of educational assessment for competency-based curriculum is a standard assessment system that is oriented to the level of mastery of competencies targeted in the curriculum. In the 2013 curriculum carried out on religious subjects, the assessment carried out was authentic assessment.